The Impact of Nuclear Energy on Environmental, Economic, and Agricultural Dynamics: New Evidence for More Sustainability - AKAR, Gökhan; AKYOL, Hikmet; SARITAŞ, Tufan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The extremes caused by climate change threaten the economic and agricultural future of nations. This research examined the impact of NE (nuclear energy) on CO2, GDP and Agro-Production Indices (API) for 24 developed and developing countries. The results of the research showed that the variables are cointegrated in the long run. The estimated results of FMOLS and AMG revealed that the use of NE reduces CO2 and increases environmental quality. In this context, our results show that NE contributes to environmental, economic and agricultural sustainability. We found that oil consumption negatively affects all API, and renewable energy (RE) consumption negatively affects agricultural and food production indices. Causality analyses showed that NE policies are compatible with environmental and RE policies. Therefore, the use of NE can play a crucial role in the transition to clean energy in research countries and in the adaptation of the agricultural sector to RE sources. In these countries, it is important to encourage policies that will reduce the dependence of the agricultural sector on fossil fuel consumption and reduce costs in the transition to clean energy sources in terms of food security and sustainable agriculture practices. The integration of nuclear energy into the agricultural sector can contribute to reducing input costs in the agricultural sector and reducing fluctuations and volatilities in food prices. In addition, the continuity of energy supply, technological innovation and infrastructure investments provided by nuclear energy can play a key role in the transition to clean energy and the achievement of the sustainable development goals of countries.